Customer Satisfaction of Service Quality: Assessing Mobile Banking Practices - Adhikari, Ujjwal; Gyawali, Santosh (Journal of Tilottama, 2023)
This study aims to examine the impact of mobile banking service quality on customer satisfaction. The research seeks to determine whether improvements in service quality lead to higher levels of customer satisfaction. Data for this study were collected through a descriptive research approach, using a structured questionnaire with close-ended questions. The survey was conducted among mobile banking users in Kapilvastu, Nepal. The statistical analysis involved employing the Chi-square test to identify associations between variables and the Mann-Whitney U test to explore the relationship of independent variables with satisfaction categories (i.e., satisfied and unsatisfied). Notably, each relationship between the variables was found to be statistically significant. The findings of this paper demonstrate that in the context of Nepal, customers indeed experience increased satisfaction with mobile banking services. In addition to creating new value for both users and providers, the digital transformation in the banking sector also raises important questions about how practices are transformed in response to these advancements. This study sheds light on the satisfaction levels of customers using mobile banking services in the Nepalese context, highlighting the positive impact of these services on customer satisfaction.